Comparative Study on Mechanical Behavior of Bamboo-Concrete Connections and Wood-Concrete Connections - Wang, Zhiyuan; Wei, Yang; Jiang, Junfeng; Zhao, Kang; Zheng, Kaiqi (Frontiers in Materials, 2020)
To investigate the similarities and differences of mechanical behavior between the bamboo-concrete connections and the wood-concrete connections, thirty-six specimens were tested through push-out tests with the material type (bamboo or wood), concrete strength and dowel diameter as test parameters. In addition to the linear variable displacement transducer (LVDT), the digital image correlation (DIC) was also used to obtain the slip distribution of the whole field of the specimens, which was conducive to the further detailed analysis of the slip distribution and a comprehensive understanding of the load-slip relationship. The results showed that the failure modes of the bamboo-concrete connections were similar to that of the wood-concrete connections, such as the concrete failure near the joint and the dowels bending in different degrees. The load-slip curves of the two kinds of connections were similar, which could be summarized as the elastic section, strengthening section and descending section. The shear stiffness and capacity of bamboo-concrete connections were higher than that of wood-concrete connections, and the shear capacity increased with the increase of dowel diameter and concrete strength. The slip distribution of the left and right sides of the specimen was basically identical. The load-transfer performance of the dowel was excellent. Finally, the prediction method of shear capacity and load-slip curve model of composite connections were proposed and verified to be effective.